UPAYA MENINGKATKAN KEMAMPUAN LITERASI BAHASA ANAK USIA 3-4 TAHUN DI KB INSAN CENDEKIA MELALUI METODE BERNYANYI DENGAN MEDIA KARTU ALFABET - Ika Wulandari; Nurhafit Kurniawan; Firman Ashadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The general purpose of this research is to improve children's language literacy skills through the application of interactive and enjoyable singing methods using alphabet card media. The specific objectives of this research are to improve children's ability to recognize letters, expand their vocabulary, understand song content, and practice listening and speaking skills through musical activities. The research method used was Classroom Action Research (CAR) with the Kemmis and McTaggart model, which consists of four stages: planning, action implementation, observation, and reflection. The research was conducted in two cycles, with 13 children aged 3-4 years in the Insan Cendekia Playgroup for the 2025/2026 academic year as the research subjects. Data were collected through observation, documentation, and field notes, then analyzed descriptively qualitatively and quantitatively. The expected outcomes of this research are the improvement of children's language literacy skills through the singing method using alphabet card media, the increased creativity of teachers in designing music-based learning, and the development of a practical guide for applying the singing method to improve early childhood literacy. The results of this research are expected to contribute to the development of active, fun, and meaningful PAUD learning.